2021
DOI: 10.1002/eap.2481
|View full text |Cite
|
Sign up to set email alerts
|

Community modeling reveals the importance of elevation and land cover in shaping migratory bird abundance in the Andes

Abstract: The tropical Andes are characterized by extreme topographic and climatic complexity, which has likely contributed to their outstanding current species diversity, composed of many range‐restricted species. However, little is known about how the distribution and abundance of highly mobile organisms, like long‐distance migratory birds, varies across different land covers, elevations, and climatic conditions within the Andes. We conducted 1,606 distance‐sampling point counts across the Colombian Andes, spanning el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 101 publications
(193 reference statements)
1
5
0
Order By: Relevance
“…Elevation niche partitioning was identified as a potential coexistence mechanism in over half of the species pairs in the community. Together with the estimated reduction in residual pairwise correlations in the extended warbler model (figure 4), these results provide strong evidence of niche partitioning along this Grinellian mechanism for ecologically similar bird species in the Virunga volcanoes, consistent with previous studies in the Cameroonian mountains [61], Himalayan highlands [26], tropical Andes [62,63] and in New Guinea highlands [64,65]. A recent survey of birds covering a third of the study area (Parc National des Volcans in Rwanda) identified 57% of species to be associated with narrow elevation bands (less than 300 m; [66]).…”
Section: Discussionsupporting
confidence: 89%
“…Elevation niche partitioning was identified as a potential coexistence mechanism in over half of the species pairs in the community. Together with the estimated reduction in residual pairwise correlations in the extended warbler model (figure 4), these results provide strong evidence of niche partitioning along this Grinellian mechanism for ecologically similar bird species in the Virunga volcanoes, consistent with previous studies in the Cameroonian mountains [61], Himalayan highlands [26], tropical Andes [62,63] and in New Guinea highlands [64,65]. A recent survey of birds covering a third of the study area (Parc National des Volcans in Rwanda) identified 57% of species to be associated with narrow elevation bands (less than 300 m; [66]).…”
Section: Discussionsupporting
confidence: 89%
“…Global amphibian declines have been the subject of much recent attention due to a range of threats including infectious disease, climate change and habitat loss (Beebee & Griffiths, 2005 ; Hof et al., 2011 ). The impacts of chytrid fungi may be the most serious risk to amphibians within the montane ecosystems of Central America and northern South America (Fisher & Garner, 2020 ) where there is also considerable attention directed towards Neotropical migrants given their use of mid‐elevation montane forests (Blake & Loiselle, 2000 ; Céspedes‐Arias et al., 2021 ). Although reducing the impact of chytrid and other diseases on amphibians requires a multifaceted approach, protecting, restoring and managing habitat is still expected to benefit amphibian populations at serious risk of extinction.…”
Section: Discussionmentioning
confidence: 99%
“…Our study region encompassed the elevation belt between 1000-2300 m asl (hereafter Montane Forest or Montane elevations). We chose this elevation belt for four reasons: 1) Several Neotropical migrants showing population declines depend on forest and agroecosystems located across that range in South America (Céspedes et al, 2021; Céspedes and Bayly, 2019; Colorado et al, 2012; González et al, 2020b; Kramer et al, 2018), 2) the range has a persistent history of loss of natural habitat driven by pastoral, agricultural and urban development that continues today across South America (Armenteras et al, 2011; Tejedor-Garavito et al, 2012), 3) drivers of habitat loss here differ from regions located below 1000 m asl (González et al, 2018, Supplemental Material Table 1), and 4) this range is the geographic focus of ongoing efforts for the conservation of declining Neotropical migrants (Partners In Flight, 2019).…”
Section: Methodsmentioning
confidence: 99%